Teachers in the perspective of idealistic philosophy: A systematic literature review - Mutiatunnisa, Dina; Masrifah, Khusnul; Mahliatussikah, Hanik (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Idealistic philosophy positions reason, morality, and the human mind as the highest forms of reality. Within this philosophical framework, teachers hold a central role as ethical exemplars and intellectual guides who shape students’ character and behavior. This systematic literature review aims to synthesize scholarly perspectives on the roles, responsibilities, and expected characteristics of teachers according to idealistic philosophy. Using a Systematic Literature Review (SLR) method, this study examined 16 relevant national and international articles published within the last decade. The analysis followed qualitative procedures involving data reduction, organization, and thematic interpretation. The findings reveal that teachers, from the viewpoint of idealistic philosophy, embody three essential dimensions: (1) Teacher obligations, which include moral superiority, mastery of knowledge, and the ability to foster active and meaningful learning; (2) Teacher responsibilities, involving guiding students’ intellectual growth, instilling ethical values, and ensuring that knowledge is translated into action; and (3) Teacher personality, encompassing integrity, intellectual excellence, communicative competence, and continuous self-development. Overall, this review highlights that idealistic philosophy emphasizes teachers as role models whose moral and intellectual authority significantly influences educational practice and student development.